PEMANTAUAN KUALITAS AIR TANAH KAWASAN PANTAI GLAGAH, KABUPATEN KULON PROGO, DI. JOGJAKARTA - Sudaryono, Sudaryono (Jurnal Teknologi Lingkungan, 2004)
As one of the state with the longest and widest coastal region in the wo, Indonesia can exploit various existing coastal resources. The agriculture term of coast outside of tide and ebb region was not many recognized, however at the last some years the coast agriculture cultivation have rapid developed not only the tide and ebb farming, but sea grass cultivation and horticulture crop and also another vegetable crop. Therefore the thing that need to get attention is possibility the presence of ground water contamination and sea water intrusion as effect of usage the manure and poisonous pesticide and ground water intake which exceeding the support power. From the result of environmental monitoring, it apparent the ground water quality in the Glagah’s coastal area was still good enough because under quality standard for drinking water, but the thing which need to get attention was the high collie bacterium content due to the usage of immature cage manure.